Development and application of an indirect ELISA and nested PCR for the epidemiological analysis of Klebsiella pneumoniae among pigs in China - Wu, Zengshuai; Li, Na; Li, Ziheng; Wang, Jianlong; Liu, Mengmeng; Qi, Mengzhu; Wei, Shaopeng; Wu, Tong; Guo, Yu; Zhu, Junhui; Jiang, Hexiang; Xue, Ruixue; et al. (Frontiers in Microbiology, 2024)
Klebsiella pneumoniae (K. pneumoniae) is an important opportunistic and zoonotic pathogen which is associated with many diseases in humans and animals. However, the pathogenicity of K. pneumoniae has been neglected and the prevalence of K. pneumoniae is poorly studied due to the lack of rapid and sensitive diagnosis techniques. In this study, we showed that infection with K. pneumoniae strain from a human patient led to mild lung injury of pigs. Subsequently, an indirect ELISA was established using the KHE protein as the coating protein for the detection of K. pneumoniae specific antibody in clinical samples. A nested PCR method to detect of nuclei acids of K. pneumoniae was also developed. For the ELISA, the optimal coating concentration of KHE protein was 10 µg/mL. The optimal dilutions of serum samples and secondary antibody were 1:100 and 1:2500, respectively. The analytical sensitivity was 1:800, with no cross-reaction between the coated antigen and porcine serum positive for antibodies against other bacteria. The intra-assay and inter-assay reproducibility coefficients of variation are less than 10%. Detection of 920 clinical porcine serum samples revealed a high K. pneumoniae infection rate by established indirect ELISA (27.28%) and nested PCR (19.13%). Moreover, correlation analysis demonstrated infection rate is positively correlated with gross population, Gross Domestic Product (GDP), and domestic tourists. In conclusion, K. pneumoniae is highly prevalent among pigs in China. Our study highlights the role of K. pneumoniae in pig health, which provides a reference for the prevention and control of diseases associated with K. pneumoniae.